PCLN-06. NOVEL TUMOR-DERIVED MODELS OF CNS HGNET-BCOR PROVIDE INSIGHTS INTO UNDERLYING MOLECULAR MECHANISMS AND INNOVATIVE THERAPEUTIC OPTIONS. Issue 2 (22nd June 2018) - Gojo, Johannes; Kirchhofer, Dominik; Lötsch, Daniela; Mohr, Thomas; Pirker, Christine; Pajtler, Kristian W; Okonechnikov, Konstantin; Englinger, Bernhard; Boidol, Bernd; Lardeau, Charles-Hugues; Czech, Thomas; Kubicek, Stefan; et al.
Abstract: Central nervous system high-grade neuroepithelial tumor with BCL6-corepressor alteration (CNS HGNET-BCOR) is a recently discovered molecular brain tumor entity characterized by genomic alterations of BCOR, a central component of a non-canonical polycomb repressive complex. However, the underlying oncogenic mechanisms and their consequences for tumor-specific anti-cancer therapy remain widely enigmatic. We systematically analyzed genomics, transcriptomics, and drug-sensitivity patterns in three tumor-derived models (two cell-lines, one primary cell-culture) from three consecutive intracranial CNS HGNET-BCOR metastases of one patient. All models harbored a unique frameshift mutation within BCOR resulting in a truncated protein lacking functionally important c-terminal protein domains. Re-expression of BCOR wild-type in our CNS HGNET-BCOR cell-models resulted in decreased cell proliferation and increased apoptosis. Interestingly, genes downregulated upon re-expression of BCOR wild-type were also derepressed in CNS HGNET-BCOR tumor tissues harboring BCOR -alterations different from our case (e.g. internal tandem duplication in BCOR ). Via comparison with a chromatin immunoprecipitation DNA-sequencing dataset, we determined that a significant proportion of the corresponding gene promoters are occupied by BCOR in BCOR wild-type cancer cells. An additional drug-screen demonstrated hypersensitivity of CNS HGNET-BCOR cells against histone deacetylase inhibitors and histone methyltransferase inhibitors. Matching of drug sensitivity patterns to upregulated target-genes determined bortezomib, dasatinib, and crizotinib as promising tumor-specific therapeutics against CNS HGNET-BCOR. Taken together, our results suggest that dysfunction of BCOR-mediated gene repression determines the oncogenic behavior and transcriptomic profile of CNS HGNET-BCOR. Moreover, we provide preliminary results for potential pharmacological interventions against this aggressive tumor type.